Carbon fiber reinforced silicon carbide ceramic and preparation method thereof
By performing functional treatment and modification of carbon fiber and silicon carbide, and cross-linking of carbon fiber and modified silicon carbide microspheres in the preparation step, the problems of poor powder dispersion and poor interface compatibility of carbon fiber reinforced silicon carbide ceramics during the preparation process are solved, and the strength, toughness and high-temperature oxidation resistance of ceramic products are improved.
Patent Information
- Application Number
- CN202510179725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-19
AI Technical Summary
During the preparation process, carbon fiber reinforced silicon carbide ceramics have problems such as poor powder dispersion and poor interfacial compatibility, which leads to insufficient strength and toughness of ceramic products. The oxidation of carbon fibers in high temperature environments affects the mechanical properties of ceramics.
By performing functional treatment of carbon fibers, including acetone soaking and citric acid solution treatment, the surface activity and binding properties of carbon fibers are improved; silicon carbide is ball milled and modified to improve its surface activity and dispersion; in the preparation step of the mixture, the uniform dispersion of carbon fibers in the silicon carbide matrix is achieved by crosslinking the functional carbon fibers with modified silicon carbide microspheres.
It improves the strength, toughness and stability of ceramic products, reduces the thermal expansion coefficient, enhances the high-temperature oxidation resistance, and improves the overall performance of ceramics.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide ceramics, and in particular relates to a carbon fiber reinforced silicon carbide ceramic and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Traditional ceramics are mainly made of clay as the main raw material and various natural minerals that are crushed, mixed, formed and calcined to make materials and various products; modern ceramics are also called new ceramics, which are often made of non-silicate chemical raw materials or artificial synthetic raw materials, such as oxides (aluminum oxide, zirconium oxide and titanium oxide, etc.) and non-oxides (silicon nitride, boron nitride, etc.); traditional ceramics are mainly used in daily necessities, building sanitation, chemical industry, electrical and other fields. With the development of the economy and the rise of high-tech industries, various new ceramics have also developed rapidly. Compared with traditional ceramics, they have better mechanical properties, temperature resistance and chemical corrosion resistance, and are widely used in various fields.
[0003] Silicon carbide ceramics are ceramics with silicon carbide as the main component. They have the advantages of good high temperature resistance, wear resistance, high hardness and relatively light density. They are widely used in aerospace, microelectronics, automobiles, atomic energy, and petrochemical industries. They are a ceramic material with great development potential and application prospects. However, due to the bonding characteristics of the molecular structure of silicon carbide itself, it lacks plastic deformation ability, making it more brittle, sensitive to defects, and has poor reliability, which seriously affects its performance as a structural material.
[0004] As a new type of high-strength, high-modulus fiber material, carbon fiber has many excellent properties. It has high axial strength and modulus, low density, high specific performance, chemical corrosion resistance, excellent thermal and electrical conductivity, small thermal expansion coefficient, and excellent electromagnetic shielding performance. It is an important ceramic reinforcement and is widely used in machinery manufacturing, aerospace, nuclear power, national defense and military industries.
[0005] When carbon fiber is used as a reinforcing phase in silicon carbide ceramics, when silicon carbide ceramics are subjected to external forces, the carbon fiber can connect the two sides of the crack like a bridge to prevent further expansion of the crack, thereby significantly improving the fracture resistance of the ceramics; during the fracture process, the carbon fiber can consume the fracture energy through mechanisms such as fiber pull-out, fiber bridging and crack deflection, thereby exerting the reinforcing and toughening effect of the carbon fiber, which can not only ensure the toughness of carbon fiber reinforced silicon carbide ceramics, but also make it have better strength performance.
[0006] However, the use of carbon fiber as a reinforcement phase in silicon carbide ceramics has the following problems: First, the interaction between silicon carbide powders is strong, the agglomeration effect is serious, the dispersion of the powder is poor, and the surface wettability of carbon fiber is poor, the inertness is large, and the surface active groups are few, which leads to the weak bonding between carbon fiber and silicon carbide matrix and poor interface compatibility, which makes it easy for ceramic products to produce macro defects and unnecessary microstructural defects during the preparation process, thereby reducing the strength performance of ceramic products; Second, carbon fiber has poor high-temperature oxidation resistance. When the temperature exceeds 400°C, the oxidation phenomenon of carbon fiber is particularly obvious, and the mass loss gradually increases, which not only affects the dimensional stability of the fiber, but also significantly reduces the mechanical properties of ceramic products. It will also increase the linear expansion coefficient, leading to stress concentration and fatigue fracture, and ultimately limit the use of ceramic products in high-temperature environments.
[0007] CN118047621A discloses a fiber-reinforced silicon carbide composite material and a preparation method thereof, wherein the raw material components include modified silicon carbide powder, silicon powder, modified carbon fiber, phenolic resin, graphite powder, a stabilizing agent, and a sintering agent; wherein the modified silicon carbide powder is obtained by coating and modifying the surface of the silicon carbide powder with dispersants hydroxyethyl cellulose, calcium carbonate, and polyacrylic acid, thereby improving the problem that the silicon carbide powder is easy to agglomerate and the like, and improving the sintering performance of the composite material; the modified carbon fiber is a modified carbon fiber coated with a graphene oxide layer, a silicon carbide layer, and a carbon nanotube layer in sequence from the inside to the outside, thereby improving the high-temperature oxidation resistance, fracture toughness, and flexural strength of the composite material; The ceramic composite material produced by this patent has improved fracture toughness and flexural strength, and the weight loss rate is 0.88% when kept at 1500℃ for 30 minutes. Although it reduces the mass loss at high temperature, the strength performance and toughness retention rate of the product in a high-temperature aerobic environment are poor, which also limits the scope of use of ceramic products. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a carbon fiber reinforced silicon carbide ceramic and a preparation method thereof, which improves the strength and toughness of ceramic products, reduces the thermal expansion coefficient, and improves high temperature oxidation resistance.
[0009] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing carbon fiber reinforced silicon carbide ceramics, including the steps of preparing functional carbon fibers, preparing modified silicon carbide microspheres, preparing a mixture, molding and calcining, and the specific operations are as follows: 1. Preparation of functional carbon fibers (1) Primary functionalization The carbon fiber is placed in acetone, the temperature is increased to 86-90°C, and the mixture is soaked for 3.7-4.2 hours. The mixture is taken out and washed, and dried at 63-67°C for 9.5-11.0 hours. The mixture is then placed in deionized water, a citric acid solution is added, the temperature is increased to 38-42°C, and the mixture is stirred for 37-44 minutes. KH550 is added, the temperature is increased to 62-67°C at a rate of 0.8-1.3°C / min, and the mixture is stirred for 4.3-4.7 hours. After the stirring is completed, the mixture is filtered out and washed, and dried at 78-82°C for 9.0-12.0 hours to obtain primary functionalized carbon fiber. The carbon fiber has a length of 0.4-0.6 μm and a diameter of 140-170 nm; The mass ratio of the carbon fiber, acetone, deionized water, citric acid solution, and kH550 is 9.7-10.3:78-83:95-106:24.3-25.4:1.30-1.35; The mass concentration of the citric acid solution is 16-20%; (2) Secondary functionalization The primary functionalized carbon fiber is placed in N, N-dimethylformamide, stirred evenly under a nitrogen atmosphere, acrylamide is added, the temperature is controlled at 58-63°C, and then ammonium persulfate and N, N'-methylenebisacrylamide are added for ultrasonic dispersion, the ultrasonic time is controlled at 37-45min, the ultrasonic power is 216-223W, and the ultrasonic frequency is 23-26kHz. After the ultrasonic treatment, the reaction is stirred at 142-155rpm for 15.5-16.3h. After the reaction is completed, the functional carbon fiber is obtained by filtering, washing, and drying. The mass ratio of the primary functionalized carbon fiber, N,N-dimethylformamide, acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide is 10.3-10.8:180-210:3.2-3.5:0.10-0.12:0.25-0.28.
[0010] 2. Preparation of modified silicon carbide microspheres The silicon carbide is placed in an ethanol solution, and sodium dodecylaminopropionate is added for ball milling. The ball milling time is 28-32 minutes, the ball milling speed is 164-175 rpm, and the ball-to-material ratio is 3-5:1. After the ball milling is completed, it is filtered out and dried at 76-80°C for 11.0-13.0 hours to obtain ball-milled silicon carbide; the ball-milled silicon carbide is placed in dimethyl sulfoxide, stirred evenly, and modified sodium alginate and hydroxyethyl cellulose are added. The temperature is raised to 70-74°C at a rate of 1.7-2.4°C / min, and tetrabutylammonium bromide is added. The reaction is kept warm for 10.0-11.5 hours. After the reaction is completed, it is filtered, washed, and dried to obtain modified silicon carbide microspheres; The particle size of the silicon carbide is 120-150nm; The mass ratio of the silicon carbide, ethanol solution and sodium dodecylaminopropionate is 12.3-12.6:115-125:1.30-1.34; The mass concentration of the ethanol solution is 27-32%; The mass volume ratio of the ball-milled silicon carbide, dimethyl sulfoxide, modified sodium alginate, hydroxyethyl cellulose and tetrabutylammonium bromide is 11.2-11.7 g: 115-124 mL: 2.0-2.3 g: 1.0-1.5 g: 0.3-0.5 g; The preparation method of the modified sodium alginate is as follows: placing sodium alginate in deionized water, stirring evenly, adding KH560, raising the temperature to 62-65° C., keeping the temperature and stirring for 2.3-2.6 hours, filtering, washing and drying after the stirring is completed to obtain the modified sodium alginate; The mass ratio of the sodium alginate, deionized water and kH560 is 9.7-10.2:105-114:1.2-1.5.
[0011] 3. Preparation of Mixture Add functional carbon fiber and modified silicon carbide microspheres to dimethyl sulfoxide, increase the temperature to 68-72°C, keep warm and stir for 5.7-6.2 hours, filter out, wash and dry to obtain a primary mixture; put the primary mixture into an ethanol solution, then add silicon nitride, graphite, zirconium oxide, phenolic resin, titanium dioxide and dioctyl sodium sulfosuccinate, and perform homogenization at a homogenization pressure of 4.7-5.3 MPa, a homogenization time of 4.0-6.0 min, and a homogenization number of 3 times. After the homogenization is completed, filter, wash and dry to obtain a mixture; The volume mass ratio of the dimethyl sulfoxide, the functional carbon fiber and the modified silicon carbide microspheres is 1000 mL: 10.5-11.0 g: 52.0-52.7 g; The mass ratio of the primary mixture, ethanol solution, silicon nitride, graphite, zirconium oxide, phenolic resin, titanium dioxide and dioctyl sodium sulfosuccinate is 62.4-63.5:214-225:3.4-3.7:4.4-4.6:5.0-5.3:8.4-8.7:1.2-1.6:0.8-1.1; The mass concentration of the ethanol solution is 23-27%.
[0012] 4. Molding and calcination The mixed material is placed in a mold, pre-tightened at a pressure of 7.8-8.2 MPa for 10-12 seconds, and then cold-pressed at 34-36 MPa for 7.5-8.5 minutes to obtain a ceramic body; the ceramic body is placed in a sintering furnace, heated to 860-880°C at a rate of 6.0-7.0°C / min in an argon atmosphere, and kept warm for 23-28 minutes, then heated to 1572-1586°C at a rate of 1.7-2.3°C / min, and kept warm for 2.4-2.6 hours, and naturally cooled to obtain carbon fiber reinforced silicon carbide ceramics.
[0013] A carbon fiber reinforced silicon carbide ceramic is prepared by adopting the preparation method.
[0014] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention uses silicon carbide as a ceramic matrix and carbon fiber as a ceramic reinforcement phase. First, the carbon fiber is functionally treated, specifically, acetone is used to soak the carbon fiber to remove colloids and impurities on the surface of the carbon fiber, and then citric acid solution and kH550 silane coupling agent are used for treatment. The citric acid solution contains hydroxyl groups, which can adhere to the surface of the carbon fiber to enhance the binding performance with the kH550 silane coupling agent, so that the surface of the carbon fiber contains more amino groups to obtain primary functionalized carbon fiber, and the primary functionalized carbon fiber is mixed with acrylamide monomer, and under the action of an initiator and a crosslinking agent, a polyacrylamide chain is formed through a polymerization reaction. The polyacrylamide chain forms a tight network structure with the carbon fiber through a crosslinking reaction, and the interface bonding strength between them is good, thereby improving the strength and stability of the ceramic material, so that the functional carbon fiber has good high-temperature antioxidant performance; in the step of preparing silicon carbide microspheres, specifically, silicon carbide is first ball-milled, and under the action of a surfactant, silicon carbide is uniformly dispersed, and under the physical impact of ball milling, defects are generated in the lattice to improve the carbon The surface activity of silicon carbide is enhanced, and then silicon carbide is mixed with modified sodium alginate and hydroxyethyl cellulose. The modified sodium alginate is prepared by modification with an epoxy silane coupling agent and contains epoxy groups. When mixed with silicon carbide, the epoxy groups of the modified sodium alginate can be cross-linked with the hydroxyl groups on the surfaces of hydroxyethyl cellulose and silicon carbide. The hydroxyethyl cellulose and silicon carbide also have good bonding properties, so that the modified sodium alginate and hydroxyethyl cellulose are evenly coated on the surface of silicon carbide, thereby improving the uniform dispersion of silicon carbide. The present invention has a certain influence on the surface activity of silicon carbide. Functional treatment is performed to modify silicon carbide microspheres, so that the dispersion of carbon fiber in the silicon carbide matrix is good. In the step of preparing the mixture, the amino group of the functional carbon fiber is cross-linked with the epoxy group of the modified silicon carbide microspheres, thereby achieving uniform dispersion of the carbon fiber in the silicon carbide matrix, improving the homogeneity of the mixture, and better exerting the strengthening and toughening effect of carbon fiber on silicon carbide, thereby improving the toughness and strength performance of the ceramic product, ensuring the stability and high temperature oxidation resistance of the ceramic product, and improving the comprehensive performance of the product; 2. The carbon fiber reinforced silicon carbide ceramics prepared by the present invention have a flexural strength of 574-579MPa and a fracture toughness of 11.9-12.3Mpa·m 1 / 2 , the thermal expansion coefficient is 1.0-1.2×10 -6 / ℃, tensile strength is 282-289MPa; 3. The carbon fiber reinforced silicon carbide ceramic prepared by the present invention is heated to 1200°C at a rate of 20°C / min in an air environment, then heated to 2000°C at a rate of 40°C / min, and kept at 2000°C for 6.0 hours. After the end of the heat preservation, it is cooled to room temperature at a rate of 40°C / min; the above operation is repeated as one cycle for 10 cycles, and the flexural strength is measured again to be 559-568MPa, and the fracture toughness is 11.5-12.0Mpa·m 1 / 2 , the tensile strength is 271-281MPa. DETAILED DESCRIPTION
[0015] In order to more clearly understand the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described: Example 1 1. Preparation of functional carbon fibers (1) Primary functionalization 10.0 g of carbon fiber was placed in 80 g of acetone, the temperature was raised to 88 ° C, and the mixture was soaked for 4.0 h. After being taken out, it was washed and dried at 65 ° C for 10.0 h. Then, it was put into 100 g of deionized water, 25.0 g of 18 wt% citric acid solution was added, the temperature was raised to 40 ° C, and the mixture was stirred for 40 min. 1.32 g of kH550 was added, the temperature was raised to 64 ° C at a rate of 1.0 ° C / min, and the mixture was stirred for 4.5 h. After the stirring was completed, it was filtered out and washed, and dried at 80 ° C for 10.0 h to obtain primary functionalized carbon fiber. The carbon fiber has a length of 0.5 μm and a diameter of 160 nm; (2) Secondary functionalization Place 10.5g of primary functionalized carbon fiber in 200g of N,N-dimethylformamide, stir evenly under a nitrogen atmosphere, add 3.4g of acrylamide, control the temperature to 60°C, then add 0.11g of ammonium persulfate and 0.26g of N,N'-methylenebisacrylamide, and perform ultrasonic dispersion. The ultrasonic time is controlled to be 40min, the ultrasonic power is 220W, and the ultrasonic frequency is 25kHz. After the ultrasonic treatment, stir the reaction at 150rpm for 16.0h. After the reaction, filter, wash, and dry to obtain functional carbon fiber.
[0016] 2. Preparation of modified silicon carbide microspheres 12.5g of silicon carbide was placed in 120g of 30wt% ethanol solution, and 1.32g of sodium dodecylaminopropionate was added for ball milling. The ball milling time was 30min, the ball milling speed was 170rpm, and the ball-to-material ratio was 4:1. After the ball milling was completed, it was filtered out and dried at 78°C for 12.0h to obtain ball-milled silicon carbide; 11.4g of ball-milled silicon carbide was placed in 120mL of dimethyl sulfoxide, stirred evenly, and then 2.1g of modified sodium alginate and 1.3g of hydroxyethyl cellulose were added. The temperature was raised to 72°C at a rate of 2.0°C / min, and 0.4g of tetrabutylammonium bromide was added. The reaction was kept warm for 11.0h. After the reaction was completed, it was filtered, washed, and dried to obtain modified silicon carbide microspheres; The particle size of the silicon carbide is 140 nm; The preparation method of the modified sodium alginate is as follows: 10.0 g of sodium alginate is placed in 110 g of deionized water, and after being stirred evenly, 1.4 g of kH560 is added, the temperature is raised to 64° C., and the mixture is stirred for 2.5 hours at the same temperature. After the stirring is completed, the mixture is filtered, washed, and dried to obtain the modified sodium alginate.
[0017] 3. Preparation of Mixture To 1000 mL of dimethyl sulfoxide, 10.7 g of functional carbon fiber and 52.3 g of modified silicon carbide microspheres were added, the temperature was raised to 70°C, the mixture was stirred for 6.0 h, filtered out, washed and dried to obtain a primary mixture; 63.0 g of the primary mixture was put into 220 g of 25 wt% ethanol solution, and then 3.6 g of silicon nitride, 4.5 g of graphite, 5.2 g of zirconium oxide, 8.6 g of phenolic resin, 1.4 g of titanium dioxide and 1.0 g of sodium dioctyl succinate sulfonate were added, and homogenization was performed at a homogenization pressure of 5.0 MPa, a homogenization time of 5.0 min, and a homogenization number of 3 times. After the homogenization, the mixture was filtered, washed and dried to obtain a mixture.
[0018] 4. Molding and calcination The mixture is placed in a mold and pre-tightened at a pressure of 8.0 MPa for 11 seconds, and then cold-pressed at 35 MPa for 8.0 minutes to obtain a ceramic body. The ceramic body is placed in a sintering furnace, and in an argon atmosphere, the temperature is increased to 870°C at a rate of 6.5°C / min, and the temperature is kept for 25 minutes. The temperature is then increased to 1580°C at a rate of 2.0°C / min, and the temperature is kept for 2.5 hours. The body is naturally cooled to obtain carbon fiber reinforced silicon carbide ceramics.
[0019] Example 2 1. Preparation of functional carbon fibers (1) Primary functionalization 9.7 g of carbon fiber was placed in 78 g of acetone, the temperature was raised to 86 ° C, and the mixture was soaked for 3.7 h. After being taken out, it was washed and dried at 63 ° C for 11.0 h. Then, it was put into 95 g of deionized water, 24.3 g of 16 wt% citric acid solution was added, the temperature was raised to 38 ° C, and the mixture was stirred for 37 min. 1.30 g of kH550 was added, the temperature was raised to 62 ° C at a rate of 0.8 ° C / min, and the mixture was stirred for 4.3 h. After the stirring was completed, it was filtered out and washed, and dried at 78 ° C for 12.0 h to obtain primary functionalized carbon fiber. The carbon fiber has a length of 0.4 μm and a diameter of 140 nm; (2) Secondary functionalization 10.3 g of primary functionalized carbon fiber was placed in 180 g of N, N-dimethylformamide, stirred evenly under a nitrogen atmosphere, 3.2 g of acrylamide was added, the temperature was controlled at 58 ° C, and then 0.10 g of ammonium persulfate and 0.25 g of N, N'-methylenebisacrylamide were added for ultrasonic dispersion. The ultrasonic time was controlled to be 37 min, the ultrasonic power was 216 W, and the ultrasonic frequency was 23 kHz. After the ultrasonic treatment, the reaction was stirred at 142 rpm for 15.5 h. After the reaction was completed, it was filtered, washed and dried to obtain functional carbon fiber.
[0020] 2. Preparation of modified silicon carbide microspheres 12.3 g of silicon carbide was placed in 115 g of 27 wt% ethanol solution, and 1.30 g of sodium dodecylaminopropionate was added for ball milling. The ball milling time was 28 min, the ball milling speed was 164 rpm, and the ball-to-material ratio was 3:1. After the ball milling was completed, it was filtered out and dried at 76 ° C for 13.0 h to obtain ball-milled silicon carbide; 11.2 g of ball-milled silicon carbide was placed in 115 mL of dimethyl sulfoxide, stirred evenly, and then 2.0 g of modified sodium alginate and 1.0 g of hydroxyethyl cellulose were added. The temperature was raised to 70 ° C at a rate of 1.7 ° C / min, and 0.3 g of tetrabutylammonium bromide was added. The reaction was kept warm for 10.0 h. After the reaction was completed, it was filtered, washed and dried to obtain modified silicon carbide microspheres; The particle size of the silicon carbide is 120 nm; The preparation method of the modified sodium alginate is as follows: 9.7 g of sodium alginate is placed in 105 g of deionized water, and after being stirred evenly, 1.2 g of KH560 is added, the temperature is raised to 62° C., and the mixture is stirred for 2.3 hours at the same temperature. After the stirring is completed, the mixture is filtered, washed, and dried to obtain the modified sodium alginate.
[0021] 3. Preparation of Mixture To 1000 mL of dimethyl sulfoxide, 10.5 g of functional carbon fiber and 52.0 g of modified silicon carbide microspheres were added, the temperature was raised to 68°C, the mixture was stirred for 5.7 h, filtered out, washed and dried to obtain a primary mixture; 62.4 g of the primary mixture was put into 214 g of 23 wt% ethanol solution, and then 3.4 g of silicon nitride, 4.4 g of graphite, 5.0 g of zirconium oxide, 8.4 g of phenolic resin, 1.2 g of titanium dioxide and 0.8 g of sodium dioctyl succinate sulfonate were added, and homogenization was performed at a homogenization pressure of 4.7 MPa, a homogenization time of 6.0 min, and a homogenization number of 3 times. After the homogenization, the mixture was filtered, washed and dried to obtain a mixture.
[0022] 4. Molding and calcination The mixture is placed in a mold and pre-tightened at a pressure of 7.8 MPa for 12 seconds, and then cold-pressed at 34 MPa for 8.5 minutes to obtain a ceramic body. The ceramic body is placed in a sintering furnace, and in an argon atmosphere, the temperature is increased to 860°C at a rate of 6.0°C / min, and the temperature is kept for 23 minutes. The temperature is then increased to 1572°C at a rate of 2.3°C / min, and the temperature is kept for 2.6 hours. The body is naturally cooled to obtain carbon fiber reinforced silicon carbide ceramics.
[0023] Example 3 1. Preparation of functional carbon fibers (1) Primary functionalization 10.3 g of carbon fiber was placed in 83 g of acetone, the temperature was raised to 90 ° C, and the mixture was soaked for 4.2 h. After being taken out, it was washed and dried at 67 ° C for 9.5 h. Then, it was put into 106 g of deionized water, 25.4 g of 20 wt% citric acid solution was added, the temperature was raised to 42 ° C, and the mixture was stirred for 44 min. 1.35 g of kH550 was added, the temperature was raised to 67 ° C at a rate of 1.3 ° C / min, and the mixture was stirred for 4.7 h. After the stirring was completed, it was filtered out and washed, and dried at 82 ° C for 9.5 h to obtain primary functionalized carbon fiber. The carbon fiber has a length of 0.6 μm and a diameter of 170 nm; (2) Secondary functionalization 10.8g of primary functionalized carbon fiber was placed in 210g of N,N-dimethylformamide, stirred evenly under a nitrogen atmosphere, 3.5g of acrylamide was added, the temperature was controlled at 63°C, and then 0.12g of ammonium persulfate and 0.28g of N,N'-methylenebisacrylamide were added for ultrasonic dispersion. The ultrasonic time was controlled to be 45min, the ultrasonic power was 223W, and the ultrasonic frequency was 26kHz. After the ultrasonic treatment, the reaction was stirred at 155rpm for 16.3h. After the reaction was completed, it was filtered, washed, and dried to obtain functional carbon fiber.
[0024] 2. Preparation of modified silicon carbide microspheres 12.6 g of silicon carbide was placed in 125 g of 32 wt% ethanol solution, and 1.34 g of sodium dodecylaminopropionate was added for ball milling. The ball milling time was 32 min, the ball milling speed was 175 rpm, and the ball-to-material ratio was 5:1. After the ball milling was completed, it was filtered out and dried at 80 ° C for 11.0 h to obtain ball-milled silicon carbide; 11.7 g of ball-milled silicon carbide was placed in 124 mL of dimethyl sulfoxide, stirred evenly, and then 2.3 g of modified sodium alginate and 1.5 g of hydroxyethyl cellulose were added. The temperature was raised to 74 ° C at a rate of 2.4 ° C / min, and 0.5 g of tetrabutylammonium bromide was added. The reaction was kept warm for 11.5 h. After the reaction was completed, it was filtered, washed and dried to obtain modified silicon carbide microspheres; The particle size of the silicon carbide is 150 nm; The preparation method of the modified sodium alginate is as follows: 10.2 g of sodium alginate is placed in 114 g of deionized water, and after being stirred evenly, 1.5 g of kH560 is added, the temperature is raised to 65° C., and the mixture is stirred for 2.6 hours at the same temperature. After the stirring is completed, the mixture is filtered, washed, and dried to obtain the modified sodium alginate.
[0025] 3. Preparation of Mixture To 1000 mL of dimethyl sulfoxide, 11.0 g of functional carbon fiber and 52.7 g of modified silicon carbide microspheres were added, the temperature was raised to 72°C, the mixture was stirred for 6.2 h, filtered out, washed and dried to obtain a primary mixture; 63.5 g of the primary mixture was put into 225 g of 27 wt% ethanol solution, and then 3.7 g of silicon nitride, 4.6 g of graphite, 5.3 g of zirconium oxide, 8.7 g of phenolic resin, 1.6 g of titanium dioxide and 1.1 g of sodium dioctyl succinate sulfonate were added, and homogenization was performed at a homogenization pressure of 5.3 MPa, a homogenization time of 4.0 min, and a homogenization number of 3 times. After the homogenization, the mixture was filtered, washed and dried to obtain a mixture.
[0026] 4. Molding and calcination The mixture is placed in a mold and pre-tightened at a pressure of 8.2 MPa for 10 seconds, and then cold-pressed at 36 MPa for 7.5 minutes to obtain a ceramic body. The ceramic body is placed in a sintering furnace, heated to 880°C at a rate of 7.0°C / min in an argon atmosphere, and kept warm for 28 minutes. The temperature is then increased to 1586°C at a rate of 1.7°C / min, and kept warm for 2.4 hours. The body is cooled naturally to obtain carbon fiber reinforced silicon carbide ceramics.
[0027] Comparative Example 1 Based on Example 1, the changes are as follows: The preparation of functional carbon fibers is omitted; in the step of preparing the mixture, the functional carbon fibers are replaced by carbon fibers that have not been treated in any way in equal amounts; The preparation method of the primary mixture is to mix 10.7g of carbon fiber and 52.3g of modified silicon carbide microspheres, stir them evenly, and prepare the primary mixture; the carbon fiber has a length of 0.5μm and a diameter of 160nm; The rest of the operations are the same.
[0028] Comparative Example 2 Based on Example 1, the changes are as follows: The step of preparing modified silicon carbide microspheres is omitted; in the step of preparing the mixture, an equal amount of modified silicon carbide microspheres is replaced by silicon carbide without any treatment; The preparation method of the primary mixture is to mix 10.7g of functional carbon fiber and 52.3g of silicon carbide, stir evenly, and prepare the primary mixture; the particle size of the silicon carbide is 140nm; The rest of the operations are the same.
[0029] Performance Testing The carbon fiber reinforced silicon carbide ceramics prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, as follows:
[0030] Among them, the high temperature oxidation resistance is that the carbon fiber reinforced silicon carbide ceramics obtained in Examples 1-3 and Comparative Examples 1-2 are heated to 1200°C at a rate of 20°C / min in an air environment, and then heated to 2000°C at a rate of 40°C / min, and kept at 2000°C for 6.0h. After the insulation, the temperature is reduced to room temperature at a rate of 40°C / min; the above operation is repeated as one cycle for 10 cycles, and the performance of the product is tested again.
[0031] The present invention uses silicon carbide as a ceramic matrix and carbon fiber as a ceramic reinforcement phase. First, the carbon fiber is functionally treated, specifically, acetone is used to soak the carbon fiber to remove colloids and impurities on the surface of the carbon fiber, and then a citric acid solution and a kH550 silane coupling agent are used for treatment. The citric acid solution contains a hydroxyl group, which can be attached to the surface of the carbon fiber to enhance the binding performance with the kH550 silane coupling agent, so that the surface of the carbon fiber contains more amino groups to obtain primary functionalized carbon fiber. The primary functionalized carbon fiber is mixed with an acrylamide monomer, and under the action of an initiator and a crosslinking agent, a polyacrylamide chain is formed through a polymerization reaction. The polyacrylamide chain forms a tight network structure with the carbon fiber through a crosslinking reaction, and the interface bonding strength between the polyacrylamide chains is good, thereby improving the strength and stability of the ceramic material, and making the functional carbon fiber have good high-temperature antioxidant performance. In the step of preparing silicon carbide microspheres, specifically, silicon carbide is firstly ball-milled, and under the action of a surfactant, the silicon carbide is uniformly dispersed, and under the physical impact of the ball milling, defects are generated in the lattice to improve the carbonization The surface activity of silicon is enhanced, and then silicon carbide is mixed with modified sodium alginate and hydroxyethyl cellulose. The modified sodium alginate is prepared by modification with an epoxy silane coupling agent and contains epoxy groups. When mixed with silicon carbide, the epoxy groups of the modified sodium alginate can cross-link with the hydroxyl groups on the surfaces of hydroxyethyl cellulose and silicon carbide. The hydroxyethyl cellulose and silicon carbide also have good bonding properties, so that the modified sodium alginate and hydroxyethyl cellulose are evenly coated on the surface of silicon carbide, thereby improving the uniform dispersion of silicon carbide. The present invention further improves the surface activity of silicon carbide and the surface activity of silicon carbide. Functional treatment is carried out and silicon carbide is modified by microspheres to make the dispersion of carbon fiber in silicon carbide matrix better. In the step of preparing the mixture, the amino group of functional carbon fiber is cross-linked with the epoxy group of modified silicon carbide microspheres, thereby achieving uniform dispersion of carbon fiber in silicon carbide matrix, improving the homogeneity of the mixture, and giving better play to the reinforcement and toughness enhancement of silicon carbide by carbon fiber, thereby improving the toughness and strength performance of ceramic products, ensuring the stability and high temperature oxidation resistance of ceramic products, and improving the comprehensive performance of products.
[0032] Comparative Example 1 omits the step of preparing functional carbon fibers, and the carbon fibers are highly inert, have poor surface wettability, and poor surface activity. In the step of preparing the mixture, they are not compatible with the silicon carbide matrix and are unevenly dispersed in the silicon carbide matrix, which affects the homogeneity of the mixture and cannot fully exert the reinforcing and toughening effects of the carbon fibers. In addition, the carbon fibers have poor high-temperature oxidation resistance, and their strength and toughness decrease rapidly in a high-temperature aerobic environment, and their stability is poor. Comparative Example 2 omits the preparation of modified silicon carbide microspheres. In the step of preparing the mixture, the silicon carbide particles have strong agglomeration forces, and when mixed with functional carbon fibers, they have poor bonding with the functional carbon fibers and cannot achieve sufficient and effective crosslinking, thereby affecting the homogeneous stability of the mixture and ultimately affecting the comprehensive performance of the ceramic product.
[0033] Unless otherwise specified, all percentages used in the present invention are by mass.
[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing carbon fiber reinforced silicon carbide ceramics, characterized in that: The method includes the steps of preparing functional carbon fiber, preparing modified silicon carbide microspheres, preparing a mixture, molding and calcining; The preparation of functional carbon fibers includes primary functionalization and secondary functionalization; The secondary functionalization step is to place the primary functionalized carbon fiber in N, N-dimethylformamide, stir evenly under a nitrogen atmosphere, add acrylamide, control the temperature to 58-63° C., then add ammonium persulfate and N, N'-methylenebisacrylamide, perform ultrasonic dispersion, and after the ultrasonication, stir the reaction for 15.5-16.3 hours. After the reaction, filter, wash, and dry to obtain the functional carbon fiber. The steps of preparing the modified silicon carbide microspheres are as follows: placing silicon carbide in an ethanol solution, adding sodium dodecylaminopropionate for ball milling, filtering out and drying after the ball milling to obtain ball-milled silicon carbide; placing the ball-milled silicon carbide in dimethyl sulfoxide, stirring evenly, adding modified sodium alginate and hydroxyethyl cellulose, heating to 70-74° C., adding tetrabutylammonium bromide, keeping the temperature for reaction for 10.0-11.5 hours, filtering, washing and drying after the reaction to obtain the modified silicon carbide microspheres.
2. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: The primary functionalization step comprises placing the carbon fiber in acetone, raising the temperature to 86-90° C., soaking for 3.7-4.2 hours, taking out and washing, drying at 63-67° C. for 9.5-11.0 hours, then placing in deionized water, adding citric acid solution, raising the temperature to 38-42° C., stirring for 37-44 minutes, adding kH550, raising the temperature to 62-67° C. at a rate of 0.8-1.3° C. / min, stirring for 4.3-4.7 hours, filtering out and washing after the stirring, and drying at 78-82° C. for 9.0-12.0 hours to obtain the primary functionalized carbon fiber.
3. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 2, characterized in that: The carbon fiber has a length of 0.4-0.6 μm and a diameter of 140-170 nm; The mass ratio of the carbon fiber, acetone, deionized water, citric acid solution, and kH550 is 9.7-10.3:78-83:95-106:24.3-25.4:1.30-1.35; The mass concentration of the citric acid solution is 16-20%.
4. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: In the secondary functionalization step, the ultrasonic dispersion has an ultrasonic time of 37-45 min, an ultrasonic power of 216-223 W, and an ultrasonic frequency of 23-26 kHz; The mass ratio of the primary functionalized carbon fiber, N,N-dimethylformamide, acrylamide, ammonium persulfate and N,N'-methylenebisacrylamide is 10.3-10.8:180-210:3.2-3.5:0.10-0.12:0.25-0.
28.
5. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: In the step of preparing modified silicon carbide microspheres, the ball milling time is 28-32 min, the ball milling speed is 164-175 rpm, and the ball-to-material ratio is 3-5:1; The particle size of the silicon carbide is 120-150nm; The mass ratio of the silicon carbide, ethanol solution and sodium dodecylaminopropionate is 12.3-12.6:115-125:1.30-1.34; The mass concentration of the ethanol solution is 27-32%; The mass volume ratio of the ball-milled silicon carbide, dimethyl sulfoxide, modified sodium alginate, hydroxyethyl cellulose and tetrabutylammonium bromide is 11.2-11.7 g: 115-124 mL: 2.0-2.3 g: 1.0-1.5 g: 0.3-0.5 g.
6. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: The preparation method of the modified sodium alginate is as follows: placing sodium alginate in deionized water, stirring evenly, adding KH560, raising the temperature to 62-65° C., keeping the temperature and stirring for 2.3-2.6 hours, filtering, washing and drying after the stirring is completed to obtain the modified sodium alginate; The mass ratio of the sodium alginate, deionized water and kH560 is 9.7-10.2:105-114:1.2-1.
5.
7. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: The steps of preparing the mixture are: adding functional carbon fiber and modified silicon carbide microspheres to dimethyl sulfoxide, raising the temperature to 68-72° C., keeping the mixture warm and stirring for 5.7-6.2 hours, filtering out, washing and drying to obtain a primary mixture; putting the primary mixture into an ethanol solution, then adding silicon nitride, graphite, zirconium oxide, phenolic resin, titanium dioxide and sodium dioctyl succinate sulfonate, and homogenizing the mixture at a homogenizing pressure of 4.7-5.3 MPa, a homogenizing time of 4.0-6.0 minutes, and three homogenizing times; after the homogenization is completed, filtering, washing and drying to obtain a mixture.
8. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 7, characterized in that: The volume mass ratio of the dimethyl sulfoxide, the functional carbon fiber and the modified silicon carbide microspheres is 1000 mL: 10.5-11.0 g: 52.0-52.7 g; The mass ratio of the primary mixture, ethanol solution, silicon nitride, graphite, zirconium oxide, phenolic resin, titanium dioxide and dioctyl sodium sulfosuccinate is 62.4-63.5:214-225:3.4-3.7:4.4-4.6:5.0-5.3:8.4-8.7:1.2-1.6:0.8-1.1; The mass concentration of the ethanol solution is 23-27%.
9. The method for preparing carbon fiber reinforced silicon carbide ceramics according to claim 1, characterized in that: The molding and calcining steps are as follows: placing the mixture in a mold, performing a pre-tightening treatment at a pressure of 7.8-8.2 MPa for 10-12 seconds, and then performing a cold pressing molding treatment at 34-36 MPa for 7.5-8.5 minutes to obtain a ceramic body; placing the ceramic body in a sintering furnace, heating the temperature to 860-880°C at a rate of 6.0-7.0°C / min in an argon atmosphere, keeping the temperature for 23-28 minutes, then heating the temperature to 1572-1586°C at a rate of 1.7-2.3°C / min, keeping the temperature for 2.4-2.6 hours, and cooling naturally to obtain carbon fiber reinforced silicon carbide ceramics.
10. Carbon fiber reinforced silicon carbide ceramics prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon fibre enhanced reaction sintering silicon carbide ceramic and preparation method thereof
CN101104559A
Preparation method of modified carbon fiber toughened silicon carbide ceramic material and modified carbon fiber toughened silicon carbide ceramic material
CN113698221A
Silicon carbide ceramic chip and preparation method thereof
CN115433018A
Fiber-reinforced silicon carbide composite material and preparation method thereof
CN118047621A
Method for preparing silicon carbide ceramic through pressureless sintering
CN118479898A
Cited By
Directional hole silicon carbide filter element and preparation method thereof
CN120662019A